First Endless Optical Polarization and Phase Tracker - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D. (2013 OPTICAL FIBER COMMUNICATION CONFERENCE AND EXPOSITION AND THE NATIONAL FIBER OPTIC ENGINEERS CONFERENCE (OFC/NFOEC))

20 krad/s endless optical polarisation and phase control - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D. (ELECTRONICS LETTERS)

An Ultralow Complexity Algorithm for Frame Synchronization and IQ Alignment in CO-OFDM Systems - Puntsri, K.; Jan, O.; Al-Bermani, A.; Woerdehoff, C.; Sandel, D.; Hussin, S.; Panhwar, M. F.; Noé, Reinhold; Rueckert, U. (2013 OPTICAL FIBER COMMUNICATION CONFERENCE AND EXPOSITION AND THE NATIONAL FIBER OPTIC ENGINEERS CONFERENCE (OFC/NFOEC))

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE PHOTONICS TECHNOLOGY LETTERS)

ISI Tolerance of Cyclic Prefix Free Coherent Optical OFDM Communication systems - Puntsri, Kidsanapong; Jan, Omar; Al-Bermani, Ali; Woerdehoff, Christian; Sandel, David; Panhwar, Muhammad Fawad; Hussin, Saleh; Rueckert, Ulrich; Noé, Reinhold (2013 ITG Symposium Proceedings - Photonic Networks)

Analysis of Partial Pilot Filling Phase Noise Compensation for CO-OFDM Systems - Hussin, Saleh; Puntsri, Kidsanapong; Noé, Reinhold (IEEE Photonics Technology Letters)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE Photonics Technology Letters)

Limit transition between hypergeometric functions of type BC and type A - Rösler, Margit; Koornwinder, Tom; Voit, Michael (Compositio Mathematica)
Abstract Let ${F}_{BC} (λ , k; t)$ be the Heckman–Opdam hypergeometric function of type BC with multiplicities $k= ({k}_{1} , {k}_{2} , {k}_{3} )$ and weighted half-sum $ρ (k)$ of positive roots. We prove that ${F}_{BC} (λ + ρ (k), k; t)$ converges as ${k}_{1} + {k}_{2} → ∞ $ and ${k}_{1} / {k}_{2} → ∞ $ to a function of type A for $t\in { \mathbb{R} }^{n} $ and $λ \in { \mathbb{C} }^{n} $ . This limit is obtained from a corresponding result for Jacobi polynomials of type BC, which is proven for a slightly more general limit behavior of the multiplicities, using an explicit representation of Jacobi polynomials in terms of Jack polynomials. Our limits include limit transitions for the spherical functions of non-compact Grassmann manifolds over one of the fields $ \mathbb{F} = \mathbb{R} , \mathbb{C} , \mathbb{H} $ when the rank is fixed and the dimension tends to infinity. The limit functions turn out to be exactly the spherical functions of the corresponding infinite-dimensional Grassmann manifold in the sense of Olshanski.
Keywords: Algebra and Number Theory

Olshanski spherical functions for infinite dimensional motion groups of fixed rank - Rösler, Margit; Voit, Michael (Journal of Lie Theory 23)

80 Gb/s Decision Feedback Equalizer for Intersymbol Interference - Möller, Lothar; Awny, Ahmed; Junio, Josef; Scheytt, Christoph; Thiede, Andreas (Optical Fiber Communication Conference)
We demonstrate the first 80 Gb/s decision feedback equalizer in various electrical and optical applications. The device, designed in SiGe:C BiCMOS 0.13 μm technology, enables error-free data recovery of heavily distorted signals transmitted at a bandwidth less than 30% of their bit rate. The fastest nonlinear electrical equalizer reported yet utilizes a novel 1-tap look-ahead architecture.

Analysis of Partial Pilot Filling Phase Noise Compensation for CO-OFDM Systems - Hussin, Saleh; Puntsri, Kidsanapong; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE PHOTONICS TECHNOLOGY LETTERS)

An Experiment of Coherent Optical DFT-spread OFDM with Laser Phase Noise - Jan, Omar; Al-Bermani, Ali; Puntsri, Kidsanapong; Sandel, David; Woerdehoff, Christian; Rueckert, Ulrich; Noé, Reinhold (2013 ITG Symposium Proceedings - Photonic Networks)

Boundary Behavior of α-Harmonic Functions on the Complement of the Sphere and Hyperplane - Luks, Tomasz (Potential Analysis)

An Interference Alignment Algorithm for Structured Channels - Lameiro, Christian; Santamaría, Ignacio (Proc. IEEE Work. Signal Process. Advances in Wireless Comm.)
In this paper we propose a new interference alignment (IA) algorithm specifically designed to work with structured channels (e.g., diagonal or block-diagonal). Multiple-input multiple-output (MIMO) structured channels arise when symbol extensions -either in time or frequency- are employed jointly with the spatial dimension in the design of the precoders. In this case, the rank constraint in the direct channels must explicitly be taken into account into the optimization problem to ensure that there is no degrees-of-freedom (DoF) loss. To this end, we propose an algorithm that minimizes the interference leakage while ensuring that the direct links are full rank and the transmitters satisfy a power constraint. The algorithm is based upon an alternating optimization procedure, which solves a generalized eigenvalue problem at each step. We show through simulations the advantages of the proposed algorithm in several scenarios that use symbols extensions or improper (a.k.a. asymmetric) signalling.

Degrees-of-Freedom for the 4-User SISO Interference Channel with Improper Signaling - Lameiro, Christian; Santamaría, Ignacio (Proc.\ IEEE Int.\ Conf.\ Comm.)
It has been recently shown that for the 3-user single-input single-output (SISO) interference channel with constant channel coefficients, a maximum of 1.2 degrees-of-freedom (DoF) are achievable using linear interference alignment schemes when improper (a.k.a. asymmetric) Gaussian signaling is applied. In this paper, we study the 4-user SISO interference channel and provide inner and outer bounds for the total number of DoF achievable for this channel. We prove that at least 4/3 DoF are achievable for the 4-user channel using also linear interference alignment techniques and improper signaling. A simple converse proof shows that no more than 8/5 DoF are achievable for this scheme. Simulation results seem to indicate that the inner bound is in fact tight for this channel, and serve to illustrate the sum-rate improvement with respect to time division multiple access (TDMA) techniques.

Optical Coherence Tomography Assessment of Vessel Wall Degradation in Aneurysmatic Thoracic Aortas - Real, Eusebio; Eguizabal, Alma; Ponton, Alejandro; Val-Bernal, J. Fernando; Mayorga, Marta; Revuelta, Jose; Lopez-Higuera, Jose; Conde, Olga (European Conferences on Biomedical Optics)
OCT images of human aorta from aneurysms reveals elastin disorder and smooth muscle cell alteration when visualizing the intima and media layers of the aortic wall. Results correlate with pathologist diagnosis in aneurysmatic and control aortas.

Quantization-loss reduction for signal parameter estimation - Stein, Manuel; Wendler, Friederike; Mezghani, Amine; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Linear classifier and textural analysis of optical scattering images for tumor classification during breast cancer extraction - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose; Conde, Olga M. (SPIE Photonics West BIOS, VIII Biomedical Applications of Light Scattering)
Texture analysis of light scattering in tissue is proposed to obtain diagnostic information from breast cancer specimens. Light scattering measurements are minimally invasive, and allow the estimation of tissue morphology to guide the surgeon in resection surgeries. The usability of scatter signatures acquired with a micro-sampling reflectance spectral imaging system was improved utilizing an empirical approximation to the Mie theory to estimate the scattering power on a per-pixel basis. Co-occurrence analysis is then applied to the scattering power images to extract the textural features. A statistical analysis of the features demonstrated the suitability of the autocorrelation for the classification of notmalignant (normal epithelia and stroma, benign epithelia and stroma, inflammation), malignant (DCIS, IDC, ILC) and adipose tissue, since it reveals morphological information of tissue. Non-malignant tissue shows higher autocorrelation values while adipose tissue presents a very low autocorrelation on its scatter texture, being malignant the middle ground. Consequently, a fast linear classifier based on the consideration of just one straightforward feature is enough for providing relevant diagnostic information. A leave-one-out validation of the linear classifier on 29 samples with 48 regions of interest showed classification accuracies of 98.74% on adipose tissue, 82.67% on non-malignant tissue and 72.37% on malignant tissue, in comparison with the biopsy H and E gold standard. This demonstrates that autocorrelation analysis of scatter signatures is a very computationally efficient and automated approach to provide pathological information in real-time to guide surgeon during tissue resection.

Fractal analysis of scatter imaging signatures to distinguish breast pathologies - Eguizabal, Alma; Laughney, Ashley M.; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose; Conde, Olga M. (SPIE Photonics West BIOS, VIII Biomedical Applications of Light Scattering)
Fractal analysis combined with a label-free scattering technique is proposed for describing the pathological architecture of tumors. Clinicians and pathologists are conventionally trained to classify abnormal features such as structural irregularities or high indices of mitosis. The potential of fractal analysis lies in the fact of being a morphometric measure of the irregular structures providing a measure of the object’s complexity and self-similarity. As cancer is characterized by disorder and irregularity in tissues, this measure could be related to tumor growth. Fractal analysis has been probed in the understanding of the tumor vasculature network. This work addresses the feasibility of applying fractal analysis to the scattering power map (as a physical modeling) and principal components (as a statistical modeling) provided by a localized reflectance spectroscopic system. Disorder, irregularity and cell size variation in tissue samples is translated into the scattering power and principal components magnitude and its fractal dimension is correlated with the pathologist assessment of the samples. The fractal dimension is computed applying the box-counting technique. Results show that fractal analysis of ex-vivo fresh tissue samples exhibits separated ranges of fractal dimension that could help classifier combining the fractal results with other morphological features. This contrast trend would help in the discrimination of tissues in the intraoperative context and may serve as a useful adjunct to surgeons.

Principal Component Analysis to extract blood oxygenation from theoretical modeling of total diffuse reflectance spectra - Eguizabal, Alma; Garcia-Allende, Pilar; Jentoft, Karin; Symvoulidis, Panagiotis; Lopez-Higuera, Jose; Ntziachristos, Vasilis; Conde, Olga M. (European Conferences on Biomedical Optics)
Endogenous tissue contrast such as decreased hemoglobin saturation aids in cancer localization. Principal component analysis is proposed for blindly oxygenation extraction from total diffuse reflectance spectra obtained by the diffusion approximation.

Input-dependent stability analysis of systems with saturation in feedback - Yu. Pogromsky, Alexander; Matveev, Alexey S.; Chaillet, Antoine; Rüffer, Björn S. (Proc. 52nd IEEE Conf. Decis. Control)
The paper deals with global stability analysis of linear control systems with saturation in feedback driven by an external input. Various new criteria based on non-quadratic Lyapunov functions are proposed, that unlike many previous results, offer better account for the role of the external excitation by providing input-dependent conditions for stability of solutions. For example, it is shown that even if the system fails to satisfy the incremental version of the circle criterion, the stability is guaranteed whenever the uniform root mean square value of the input signal is less than a computable threshold. The general theoretical results are illustrated in the case of the double integrator closed by a saturated linear feedback with an external excitation.

Linear equalization in communications with mismatched modeling using Krylov subspace expansion - Tong, Jun; Schreier, Peter J. (Proc. IEEE Wireless Comm. Networking Conf. (WCNC))

Martin representation and Relative Fatou Theorem for fractional Laplacian with a gradient perturbation - Graczyk, Piotr; Jakubowski, Tomasz; Luks, Tomasz (Positivity)

Locally Most Powerful Invariant Tests for Correlation and Sphericity of Gaussian Vectors - Ramírez, D.; Vía, J.; Santamaría, I.; Scharf, L. L. (IEEE Trans.\ Inform.\ Theory)
In this paper we study the existence of locally most powerful invariant tests (LMPIT) for the problem of testing the covariance structure of a set of Gaussian random vectors. The LMPIT is the optimal test for the case of close hypotheses, among those satisfying the invariances of the problem, and in practical scenarios can provide better performance than the typically used generalized likelihood ratio test (GLRT). The derivation of the LMPIT usually requires one to find the maximal invariant statistic for the detection problem and then derive its distribution under both hypotheses, which in general is a rather involved procedure. As an alternative, Wijsman’s theorem provides the ratio of the maximal invariant densities without even finding an explicit expression for the maximal invariant. We first consider the problem of testing whether a set of N-dimensional Gaussian random vectors are uncorrelated or not, and show that the LMPIT is given by the Frobenius norm of the sample coherence matrix. Second, we study the case in which the vectors under the null hypothesis are uncorrelated and identically distributed, that is, the sphericity test for Gaussian vectors, for which we show that the LMPIT is given by the Frobenius norm of a normalized version of the sample covariance matrix. Finally, some numerical examples illustrate the performance of the proposed tests, which provide better results than their GLRT counterparts.

Amplify-and-Forward Strategies in the Two-Way Relay Channel with Analog Tx-Rx Beamforming - Lameiro, Christian; Vía, Javier; Santamaría, Ignacio (IEEE Trans. Veh. Techn.)
In this paper, we study the multiple-input multiple-output two-way relay channel (MIMO-TWRC) when the nodes and relay use analog beamforming. Following the amplify-andforward (AF) strategy, the problem consists of finding the transmit and receive beamformers of the nodes and relay (as well as the power allocated to each one) that achieve the boundary of the optimal rate region. To solve it, we first express the optimal node beamformers in terms of relay beamformers and then show that the optimal rate region can efficiently be characterized using convex optimization techniques. We also extend our study to the multiple-relay scenario when the source nodes are single antenna and propose a distributed algorithm to compute the relay beamforming matrices. The proposed algorithm consists of solving two different subproblems. First, each individual TWRC is optimized independently. Next, a distributed beamforming is applied to make the signals from the relays add up coherently at the source nodes. Numerical examples are provided to illustrate the performance of the proposed techniques and to compare the performance of analog beamforming architectures against conventional MIMO schemes that operate at the baseband.

Computing the Degrees of Freedom for Arbitrary MIMO Interference Channels - Lameiro, Christian; Vía, Javier; Beltrán, Carlos; Santamaría, Ignacio (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
In this paper we provide an efficient procedure to compute the total number of degrees of freedom (DoF), achievable by linear beamforming, of the $K$-user multiple-input multiple-output (MIMO) interference channel with an arbitrary number of Tx-Rx antennas at each link. Firstly, we derive an analytical outer bound that generalizes the results that exist for the symmetric $K$-user $M\timesN$ interference channel. Secondly, we obtain a tighter bound by solving a convex optimization problem that includes as constraints the DoF characterizations for point-to-point MIMO links and for 2-user interference channels. The solution to this convex problem admits an interesting waterfilling interpretation. Finally, exploiting this outer bound and using a recently proposed feasibility test, we show that it is possible to obtain the DoF for any interference channel in an efficient way. Some simulations results are included to illustrate the tightness of the derived bounds, as well as to study the DoF achievable for the 4-user channel when we distribute the total number of antennas among users and between transmitters and receivers in different ways.

Robust stability of networks of iISS systems: Construction of sum-type Lyapunov functions - Ito, Hiroshi; Jiang, Zhong-Ping; Dashkovskiy, Sergey; Rüffer, Björn S. (IEEE Trans. Autom. Control)
This paper gives a solution to the problem of verifying stability of networks consisting of integral input-to-state stable (iISS) subsystems. The iISS small-gain theorem developed recently has been restricted to interconnections of two subsystems. For large-scale systems, stability criteria relying only on gain-type information that were previously developed address only input-to-state stable (ISS) subsystems. To address the stability problem involving iISS subsystems interconnected in general structure, this paper shows how to construct Lyapunov functions of the network by means of a sum of nonlinearly rescaled individual Lyapunov functions of subsystems under an appropriate small-gain condition.

Power-CCA: Maximizing the Correlation Coefficient between the Power of Projections - Ramírez, D.; Schreier, P. J.; Vía, J.; Nikulin, V. V. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
This work presents a variation of canonical correlation analysis (CCA), where the correlation coefficient between the instantaneous power of the projections is maximized, rather than between the projections themselves. The resulting optimization problem is not convex, and we have to resort to a sub-optimal approach. Concretely, we propose a two-step solution consisting of the singular value decomposition (SVD) of a "coherence" matrix followed by a rank-one matrix approximation. This technique is applied to blindly recovering signals in a model that is motivated by the study of neuronal dynamics in humans using electroencephalography (EEG) and magnetoencephalography (MEG). A distinctive feature of this model is that it allows recovery of amplitude-amplitude coupling between neuronal processes.

Quantization-loss analysis for array signal-source localization - Stein, Manuel; Mezghani, Amine; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Quantization-loss reduction for 1-bit BOC positioning - Wendler, Friederike; Stein, Manuel; Mezghani, Amine; Nossek, Josef A. (ION Int.\ Tech. Meet.)

A unified framework for regularized linear estimation in communication systems - Tong, Jun; Schreier, Peter J. (Signal Process.)
Two concerns often arise simultaneously when applying linear estimation in communication systems: the computational complexity can be prohibitively high when the system size is large, and the performance may degrade dramatically when the presumed model is mismatched with the actual system. In this paper, we introduce a subspace expansion framework to jointly address these concerns, in which the observation is first projected onto a lower-dimensional subspace and then the solution of the projected problem is regularized. We discuss two projection methods based on eigensubspace and Krylov subspace expansions. We show that the Krylov subspace projection provides an economical solution to regularized linear estimation. We also compare different regularization methods, such as principal components and diagonal loading. We show that diagonal loading generally outperforms other alternatives and that Krylov subspace rank reduction can yield a regularization effect close to diagonal loading. Finally, we investigate the impact of preconditioning on the performance and complexity for mismatched modeling and propose a loaded preconditioner, which can reduce complexity as well as preserve the regularization effect. Under the proposed framework, various regularization schemes are studied and some guidelines for choosing the right scheme are provided.

A Two-Phase Approach to Stability of Networks Given in iISS Framework: Utilization of a Matrix-Like Criterion - Ito, Hiroshi; Rüffer, Björn S. (Proc. IEEE American Contr. Conf.)
This article is concerned with global asymptotic stability (GAS) of dynamical networks. The case when subsystems are integral input-to-state stable (iISS) has been recognized as notoriously difficult to deal with in the literature. In fact, the lack of energy dissipation for large input denies direct application of the small-gain argument for input-to-state stable (ISS) subsystems. Here for networks consisting of iISS subsystems it is demonstrated that a two-phase approach allows us to make use of the ISS small-gain argument by separating a trajectory into a transient and a subsequent convergence. In contrast to the previous iISS results, the two-phase approach immediately leads to a sufficient criterion for GAS of general nonlinear networks in a matrix-like form (order condition).

Convergent Systems vs. Incremental Stability - Rüffer, Björn S.; van de Wouw, Nathan; Mueller, Markus (Systems Control Lett.)
Two similar stability notions are considered; one is the long established notion of convergent systems, the other is the younger notion of incremental stability. Both notions require that any two solutions of a system converge to each other. Yet these stability concepts are different, in the sense that none implies the other, as is shown in this paper using two examples. It is shown under what additional assumptions one property indeed implies the other. Furthermore, this paper contains necessary and sufficient characterizations of both properties in terms of Lyapunov functions.

A Razumikhin approach for the incremental stability of delayed nonlinear systems - Chaillet, Antoine; Yu. Pogromsky, Alexander; Rüffer, Björn S. (Proc. 52nd IEEE Conf. Decis. Control)
This paper provides sufficient conditions for the incremental stability of time-delayed nonlinear systems. It relies on the Razumikhin-Lyapunov approach, which consists in invoking small-gain arguments by treating the delayed state as a feedback perturbation. The results are valid for multiple delays, as well as bounded time-varying delays. We provide conditions under which the limit solution of a time-delayed nonlinear system to a periodic (resp. constant) input is itself periodic and of the same period (resp. constant). As an illustration, a specific focus is given on a class of delayed Lur’e systems.

Optical coherence tomography assessment of vessel wall degradation in thoracic aortic aneurysms - Real, Eusebio; Eguizabal, Alma; Pontón, Alejandro; Díez, Marta Calvo; Val-Bernal, José Fernando; Mayorga, Marta; Revuelta, José M.; López-Higuera, José M.; Conde, Olga M. (J. Biomed. Opt.)

Separable Lyapunov functions for monotone systems - Rantzer, Anders; Rüffer, Björn S.; Dirr, Gunther (Proc. 52nd IEEE Conf. Decis. Control)
Separable Lyapunov functions play vital roles, for example, in stability analysis of large-scale systems. A Lyapunov function is called max-separable if it can be decomposed into a maximum of functions with one-dimensional arguments. Similarly, it is called sum-separable if it is a sum of such functions. In this paper it is shown that for a monotone system on a compact state space, asymptotic stability implies existence of a max-separable Lyapunov function. We also construct two systems on a non-compact state space, for which a max-separable Lyapunov function does not exist. One of them has a sum-separable Lyapunov function. The other does not.

Regularized Preconditioning for Krylov Subspace Equalization of OFDM Systems over Doubly Selective Channels - Tong, Jun; Schreier, Peter J. (IEEE Wireless Comm. Lett.)

Joint space-time interference mitigation for embedded multi-antenna GNSS receivers - Castañeda, Mario; Stein, Manuel; Antreich, Felix; Tasdemir, Emrah; Kurz, Lothar; Noll, Tobias G.; Nossek, Josef A. (ION GNSS+)

Direct identification of breast cancer pathologies using blind separation of label-free localized reflectance measurements - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (Biomed. Opt. Express)
Breast tumors are blindly identified using Principal (PCA) and Independent Component Analysis (ICA) of localized reflectance measurements. No assumption of a particular theoretical model for the reflectance needs to be made, while the resulting features are proven to have discriminative power of breast pathologies. Normal, benign and malignant breast tissue types in lumpectomy specimens were imaged ex vivo and a surgeon-guided calibration of the system is proposed to overcome the limitations of the blind analysis. A simple, fast and linear classifier has been proposed where no training information is required for the diagnosis. A set of 29 breast tissue specimens have been diagnosed with a sensitivity of 96% and specificity of 95% when discriminating benign from malignant pathologies. The proposed hybrid combination PCA-ICA enhanced diagnostic discrimination, providing tumor probability maps, and intermediate PCA parameters reflected tissue optical properties.

A millimeter wave quad-phase ring oscillator using 0.13 µm SiGe BiCMOS HBT technology - Ali, U.; Thiede, Andreas (2013 International Semiconductor Conference Dresden - Grenoble (ISCDG))

Approximation, Proof Systems, and Correlations in a Quantum World - Gharibian, Sevag
This thesis studies three topics in quantum computation and information: The approximability of quantum problems, quantum proof systems, and non-classical correlations in quantum systems. In the first area, we demonstrate a polynomial-time (classical) approximation algorithm for dense instances of the canonical QMA-complete quantum constraint satisfaction problem, the local Hamiltonian problem. In the opposite direction, we next introduce a quantum generalization of the polynomial-time hierarchy, and define problems which we prove are not only complete for the second level of this hierarchy, but are in fact hard to approximate. In the second area, we study variants of the interesting and stubbornly open question of whether a quantum proof system with multiple unentangled quantum provers is equal in expressive power to a proof system with a single quantum prover. Our results concern classes such as BellQMA(poly), and include a novel proof of perfect parallel repetition for SepQMA(m) based on cone programming duality. In the third area, we study non-classical quantum correlations beyond entanglement, often dubbed "non-classicality". Among our results are two novel schemes for quantifying non-classicality: The first proposes the new paradigm of exploiting local unitary operations to study non-classical correlations, and the second introduces a protocol through which non-classical correlations in a starting system can be "activated" into distillable entanglement with an ancilla system. An introduction to all required linear algebra and quantum mechanics is included.

QMA variants with polynomially many provers - Gharibian, Sevag; Sikora, Jamie; Upadhyay, Sarvagya (Quantum Information & Computation)
We study three variants of multi-prover quantum Merlin-Arthur proof systems. We first show that the class of problems that can be efficiently verified using polynomially many quantum proofs, each of logarithmic-size, is exactly MQA (also known as QCMA), the class of problems which can be efficiently verified via a classical proof and a quantum verifier. We then study the class BellQMA(poly), characterized by a verifier who first applies unentangled, nonadaptive measurements to each of the polynomially many proofs, followed by an arbitrary but efficient quantum verification circuit on the resulting measurement outcomes. We show that if the number of outcomes per nonadaptive measurement is a polynomially-bounded function, then the expressive power of the proof system is exactly QMA. Finally, we study a class equivalent to QMA(m), denoted SepQMA(m), where the verifier's measurement operator corresponding to outcome "accept" is a fully separable operator across the m quantum proofs. Using cone programming duality, we give an alternate proof of a result of Harrow and Montanaro [FOCS, pp. 633--642 (2010)] that shows a perfect parallel repetition theorem for SepQMA(m) for any m.

Self-organization of nanospheres in trenches on silicon surfaces - Brassat, Katharina; Assion, Fabian; Hilleringmann, Ulrich; Lindner, Jörg K. N. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Titanium Disilicide as High-Temperature Contact Material for Thermoelectric Generators - Assion, F.; Schönhoff, M.; Hilleringmann, Ulrich (Journal of Electronic Materials)
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Enhanced organic light-emitting diode based on a columnar liquid crystal by integration in a microresonator - Kasdorf, Olga; Vollbrecht, Joachim; Ohms, Benjamin; Hilleringmann, Ulrich; Bock, Harald; Kitzerow, Heinz-S. (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

On an analogue to the Lucas-Lehmer-Riesel test using elliptic curves - Kirschmer, Markus; Mertens, Michael H. (Integers)
Following an idea of B. H. Gross, who presented an elliptic curve test for Mersenneprimes Mₚ=2ᵖ−1, we propose a similar test with elliptic curves for generalizedThabit primesK(h, n) := h·2ⁿ−1 for any positive odd number h and any integer n> log₂(h)+2.

Design and implementation of a measurement system for automatically measurement of electrical parameters of thermoelectric generators - Petrov, Dmitry; Assion, Fabian; Hilleringmann, Ulrich (MRS Proceedings)
ABSTRACT The continues development of thermoelectric generators causes a permanent improvement of their characteristics. New types of thermoelectric generators can work at temperatures up to 1000 K. With this, special measurement equipment is needed to control the electrical parameters of the new developed specimens. The devices must be tested over the whole range of operating temperatures. For each temperature value a series of electrical measurements has to be performed. To establish the maximal output power of the thermoelectric generators, a load resistor with variable resistance has to be connected to the output of thermoelectric generator. The measurement system should measure the electrical current through the load resistor and the voltage over this resistor to determine the device parameters. A large amount of measurement data have to be collected and processed to evaluate the electrical characteristics of the specimen and to present them in graphical form, suitable for the comparison with others specimens.
Keywords: General Engineering

Formation and Properties of TiSi2 as Contact Material for High-Temperature Thermoelectric Generators - Assion, Fabian; Schönhoff, Marcel; Hilleringmann, Ulrich (MRS Proceedings)
ABSTRACT Thermoelectric generators (TEG) are capable of transforming waste heat directly into electric power. With higher temperatures the yield of the devices rises which makes high-temperature contact materials important. The formation of titanium disilicide (TiSi 2 ) and its properties were analyzed and optimized for the use in TEG. Depending on a direct or an indirect transformation into the C54 crystal structure the process forms a layer with a resistivity of 20-22 μΩcm. Process gases influence the resistivity and result in difference of 20 %. The growing rate of TiSi 2 on silicon dioxide was determined; it shows a strong dependence on the used atmosphere and temperature. A maximum overgrowing length of 30 μm was found.
Keywords: General Engineering

Electrical characterization of rubber mixture sheets based on a coaxial probe method in combination with 3D electromagnetic simulation model - Kanwar, K.; Fischer, C.; Geneiss, V.; Mager, T.; Ballhausen, U.; Hedayat, C.; Hilleringmann, Ulrich (2012 IEEE International Conference on RFID-Technologies and Applications (RFID-TA))

Enhanced event-driven modeling of a CP-PLL with nonlinearities and nonidealities - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (2013 IEEE 56th International Midwest Symposium on Circuits and Systems (MWSCAS))

Resistivity reduction in flexible dye sensitized solar cells by UV irradiation and carbon nanotubes - Hilleringmann, Ulrich; Ohms, B.; Kleine, A. (2013 IEEE International Conference on Industrial Technology (ICIT))

Characterization and Analysis of the Hysteresis in a ZnO Nanoparticle Thin-Film Transistor - Vidor, F. F.; Wirth, G.; Assion, F.; Wolff, K.; Hilleringmann, Ulrich (IEEE Transactions on Nanotechnology)
Keywords: Electrical and Electronic Engineering; Computer Science Applications

Design and analysis of UHF RFID tag for a rubber transmission belt based on 3D electrical model - Kanwar, K.; Geneiss, V.; Mager, T.; Scheele, S.; Ballhausen, U.; Hedayat, C.; Hilleringmann, Ulrich (2013 21st International Conference on Software, Telecommunications and Computer Networks - (SoftCOM 2013))

Designing output-power-optimized thermoelectric generators via analytic and finite element method modelling - Assion, F.; Fischer, C.; Schonhof, M.; Hilleringmann, Ulrich; Hedayat, C. (2013 IEEE International Conference on Industrial Technology (ICIT))

Enhanced organic light-emitting diode based on a columnar liquid crystal by integration in a microresonator - Kasdorf, Olga; Vollbrecht, Joachim; Ohms, Benjamin; Hilleringmann, Ulrich; Bock, Harald; Kitzerow, Heinz-Siegfried (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Single-class genera of positive integral lattices - Lorch, David; Kirschmer, Markus (LMS Journal of Computation and Mathematics)
We give an enumeration of all positive definite primitive Z-lattices in dimension n ≥ 3 whose genus consists of a single isometry class. This is achieved by using bounds obtained from the Smith–Minkowski–Siegel mass formula to computationally construct the square-free determinant lattices with this property, and then repeatedly calculating pre-images under a mapping first introduced by G. L. Watson. We hereby complete the classification of single-class genera in dimensions 4 and 5 and correct some mistakes in Watson’s classifications in other dimensions. A list of all single-class primitive Z-lattices has been compiled and incorporated into the Catalogue of Lattices.
Keywords: Computational Theory and Mathematics; General Mathematics

Collective effects in second-harmonic generation from split-ring-resonator arrays - Niesler, Fabian B.; Linden, Stefan; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, Martin (Conference on Lasers and Electro-Optics 2012)
We perform experiments on resonant second-harmonic generation from planar gold split-ring-resonator arrays under normal incidence of light as a function of the lattice constant. Optimum nonlinear conversion occurs at intermediate lattice constants.
Keywords: tet_topic_shg; tet_topic_meta

Optimal second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVII)
Previous experimental measurements and numerical simulations give evidence of strong electric and magnetic field interaction between split-ring resonators in dense arrays. One can expect that such interactions have an influence on the second harmonic generation. We apply the Discontinuous Galerkin Time Domain method and the hydrodynamic Maxwell-Vlasov model to simulate the linear and nonlinear optical response from SRR arrays. The simulations show that dense placement of the constituent building blocks appears not always optimal and collective effects can lead to a significant suppression of the near fields at the fundamental frequency and, consequently, to the decrease of the SHG intensity. We demonstrate also the great role of the symmetry degree of the array layout which results in the variation of the SHG efficiency in range of two orders of magnitude.
Keywords: tet_topic_shg; tet_topic_meta

Composition algebra of a weighted projective line - Burban, Igor; Schiffmann, O. (Journal für Reine und Angew. Mathematik)

BS 1149.1 extensions for an online interconnect fault detection and recovery - Sadeghi-Kohan, Somayeh; Namaki-Shoushtari, Majid; Javaheri, Fatemeh; Navabi, Zainalabedin (2012 IEEE International Test Conference)

A new structure for interconnect offline testing - Sadeghi-Kohan, Somayeh; Keshavarz, Shahrzad; Zokaee, Farzaneh; Farahmandi, Farimah; Navabi, Zainalabedin (East-West Design & Test Symposium (EWDTS 2013))

FPGA-accelerated Key Search for Cold-Boot Attacks against AES - Riebler, Heinrich; Kenter, Tobias; Sorge, Christoph; Plessl, Christian (Proceedings of the International Conference on Field-Programmable Technology (FPT))
Cold-boot attacks exploit the fact that DRAM contents are not immediately lost when a PC is powered off. Instead the contents decay rather slowly, in particular if the DRAM chips are cooled to low temperatures. This effect opens an attack vector on cryptographic applications that keep decrypted keys in DRAM. An attacker with access to the target computer can reboot it or remove the RAM modules and quickly copy the RAM contents to non-volatile memory. By exploiting the known cryptographic structure of the cipher and layout of the key data in memory, in our application an AES key schedule with redundancy, the resulting memory image can be searched for sections that could correspond to decayed cryptographic keys; then, the attacker can attempt to reconstruct the original key. However, the runtime of these algorithms grows rapidly with increasing memory image size, error rate and complexity of the bit error model, which limits the practicability of the approach.In this work, we study how the algorithm for key search can be accelerated with custom computing machines. We present an FPGA-based architecture on a Maxeler dataflow computing system that outperforms a software implementation up to 205x, which significantly improves the practicability of cold-attacks against AES.
Keywords: coldboot

On-The-Fly Computing: A Novel Paradigm for Individualized IT Services - Happe, Markus; Kling, Peter; Plessl, Christian; Platzner, Marco; Meyer auf der Heide, Friedhelm (Proceedings of the 9th IEEE Workshop on Software Technology for Future embedded and Ubiquitous Systems (SEUS))
In this paper we introduce “On-The-Fly Computing”, our vision of future IT services that will be provided by assembling modular software components available on world-wide markets. After suitable components have been found, they are automatically integrated, configured and brought to execution in an On-The-Fly Compute Center. We envision that these future compute centers will continue to leverage three current trends in large scale computing which are an increasing amount of parallel processing, a trend to use heterogeneous computing resources, and—in the light of rising energy cost—energy-efficiency as a primary goal in the design and operation of computing systems. In this paper, we point out three research challenges and our current work in these areas.

Parallel Macro Pipelining on the Intel SCC Many-Core Computer - Suess, Tim; Schoenrock, Andrew; Meisner, Sebastian; Plessl, Christian (Proc. Int. Symp. on Parallel and Distributed Processing Workshops (IPDPSW))

DoA-Based Microphone Array Position Self-Calibration Using Circular Statistic - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2013))
In this paper we propose an approach to retrieve the absolute geometry of an acoustic sensor network, consisting of spatially distributed microphone arrays, from reverberant speech input. The calibration relies on direction of arrival measurements of the individual arrays. The proposed calibration algorithm is derived from a maximum-likelihood approach employing circular statistics. Since a sensor node consists of a microphone array with known intra-array geometry, we are able to obtain an absolute geometry estimate, including angles and distances. Simulation results demonstrate the effectiveness of the approach.
Keywords: Geometry calibration; microphone arrays; position self-calibration

Sampling Rate Synchronisation in Acoustic Sensor Networks with a Pre-Trained Clock Skew Error Model - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a combined hardware/software approach for synchronizing the sampling clocks of an acoustic sensor network. A first clock frequency offset estimate is obtained by a time stamp exchange protocol with a low data rate and computational requirements. The estimate is then postprocessed by a Kalman filter which exploits the specific properties of the statistics of the frequency offset estimation error. In long term experiments the deviation between the sampling oscillators of two sensor nodes never exceeded half a sample with a wired and with a wireless link between the nodes. The achieved precision enables the estimation of time difference of arrival values across different hardware devices without sharing a common sampling hardware.
Keywords: synchronization; acoustic sensor network

The Directed Search Method for Pareto Front Approximations with Maximum Dominated Hypervolume - Sosa, Hernández V; Schütze, O; Rudolph, G; Trautmann, Heike (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation IV)
In many applications one is faced with the problem that multiple objectives have to be optimized at the same time. Since typically the solution set of such multi-objective optimization problems forms a manifold which cannot be computed analytically, one is in many cases interested in a suitable finite size approximation of this set. One widely used approach is to find a representative set that maximizes the dominated hypervolume that is defined by the images in objective space of these solutions and a given reference point. In this paper, we propose a new point-wise iterative search procedure, Hypervolume Directed Search (HVDS), that aims to increase the hypervolume of a given point in an archive for bi-objective unconstrained optimization problems. We present the HVDS both as a standalone algorithm and as a local searcher within a specialized evolutionary algorithm. Numerical results confirm the strength of the novel approach.

Finding Evenly Spaced Pareto Fronts for Three-Objective Optimization Problems - Trautmann, Heike; Rudolph, G; Dominguez-Medina, C; Schütze, O (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation II)
The averaged Hausdorff distance Δ p is a performance indicator in multi-objective evolutionary optimization which simultaneously takes into account proximity to the true Pareto front and uniform spread of solutions. Recently, the multi-objective evolutionary algorithm Δ p -EMOA was introduced which successfully generates evenly spaced Pareto front approximations for bi-objective problems by integrating an external archiving strategy into the SMS-EMOA based on Δ p . In this work a conceptual generalization of the Δ p -EMOA for higher objective space dimensions is presented and experimentally compared to state-of-the art EMOA as well as specialized EMOA variants on three-dimensional optimization problems.

A Feature-Based Comparison of Local Search and the Christofides Algorithm for the Travelling Salesperson Problem - Nallaperuma, Samadhi; Wagner, Markus; Neumann, Frank; Bischl, Bernd; Mersmann, Olaf; Trautmann, Heike (Proceedings of the Twelfth Workshop on Foundations of Genetic Algorithms XII)
Understanding the behaviour of well-known algorithms for classical NP-hard optimisation problems is still a difficult task. With this paper, we contribute to this research direction and carry out a feature based comparison of local search and the well-known Christofides approximation algorithm for the Traveling Salesperson Problem. We use an evolutionary algorithm approach to construct easy and hard instances for the Christofides algorithm, where we measure hardness in terms of approximation ratio. Our results point out important features and lead to hard and easy instances for this famous algorithm. Furthermore, our cross-comparison gives new insights on the complementary benefits of the different approaches.
Keywords: approximation algorithms; local search; traveling salesperson problem; feature selection; prediction; classification

Evenly Spaced Pareto Front Approximations for Tricriteria Problems Based on Triangulation - Rudolph, G; Trautmann, Heike; Sengupta, S; Schütze, O (Evolutionary Multi-Criterion Optimization — 7$^th$ International Conference, EMO 2013, Sheffield, UK, Proceedings)
In some technical applications like multiobjective online control an evenly spaced approximation of the Pareto front is desired. Since standard evolutionary multiobjective optimization (EMO) algorithms have not been designed for that kind of approximation we propose an archive-based plug-in method that builds an evenly spaced approximation using averaged Hausdorff measure between archive and reference front. In case of three objectives this reference font is constructed from a triangulated approximation of the Pareto front from a previous experiment. The plug-in can be deployed in online or offline mode for any kind of EMO algorithm.

Directed Search Method for Indicator-based Multi-objective Evolutionary Algorithms - Sosa-Hernandez, VA; Schütze, O; Rudoph, G; Trautmann, Heike (Proceeding of the Fifteenth Annual Conference Companion on Genetic and Evolutionary Computation Conference Companion)
Indicator based evolutionary algorithms have caught the interest of many researchers for the treatment of multi-objective optimization problems in the recent past since they deliver the desired approximation of the solution set and due to a usually better performance compared to dominance based algorithms. Nevertheless, these methods still suffer the drawback that many function evaluations are required to obtain a suitable representation of the solution set. The aim of this study is to present the Directed Search (DS) Method as local searcher within global indicator based optimization algorithms. For this, we will present the DS in the context of hypervolume maximization leading to both a new local search algorithm and a new memetic algorithm. Further, we will present first attempts to adapt the DS to a class of parameter dependent problems.

Evenly spaced Pareto fronts of quad-objective problems using PSA partitioning technique - Dominguez-Medina, C; Rudolph, G; Schütze, O; Trautmann, Heike (Proceedings of the 2013 IEEE Congress on Evolutionary Computation (CEC))
Here we address the problem of computing finite size Hausdorff approximations of the Pareto front of four-objective optimization problems by means of evolutionary computing. Since many applications desire an approximation evenly spread along the Pareto front and approximations that are good in the Hausdorff sense are typically evenly spread along the Pareto front we consider three different evolutionary multi-objective algorithms tailored to that purpose, where two of them are based on the Part and Selection Algorithm (PSA). Finally, we present some numerical results indicating the strength of the novel methods.

Reactive strategy choice in StarCraft by means of Fuzzy Control - Preuss, Mike; Kozakowski, Daniel; Hagelbäck, Johan; Trautmann, Heike (2013 IEEE Conference on Computational Inteligence in Games (CIG))
Current StarCraft bots are not very flexible in their strategy choice, most of them just follow a manually optimized one, usually a rush. We suggest a method of augmenting existing bots via Fuzzy Control in order to make them react on the current game situation. According to the available information, the best matching of a pool of strategies is chosen. While the method is very general and can be applied easily to many bots, we implement it for the existing BTHAI bot and show experimentally how the modifications affects its gameplay, and how it is improved compared to the original version.

Indicator-based Selection in Evolutionary Multiobjective Optimization Algorithms Based On the Desirability Index - Trautmann, Heike; Wagner, T; Biermann, D; Weihs, C (Journal of Multi-Criteria Decision Analysis)
In multiobjective optimization, the identification of practically relevant solutions on the Pareto-optimal front is an important research topic. Desirability functions (DFs) allow the preferences of the decision maker to be specified in an intuitive way. Recently, it has been shown for continuous optimization problems that an a priori transformation of the objectives by means of DFs can be used to focus the search of a hypervolume-based evolutionary algorithm on the desired part of the front. In many-objective optimization, however, the computational complexity of the hypervolume can become a crucial part. Thus, an alternative to this approach will be presented in this paper. The new algorithm operates in the untransformed objective space, but the desirability index (DI), that is, a DF-based scalarization, will be used as the second-level selection criterion in the non-dominated sorting. The diversity and uniform distribution of the resulting approximation are ensured by the use of an external archive. In the experiments, different preferences are specified as DFs, and their effects are investigated. It is shown that trade-off solutions are generated in the desired regions of the Pareto-optimal front and with a density adaptive to the DI. The efficiency of the approach with respect to increasing objective space dimension is also analysed using scalable test functions. The convergence speed is superior to other set-based and preference-based evolutionary multiobjective algorithms while the approach is of low computational complexity due to cheap DI evaluations. Copyright © 2013 John Wiley & Sons, Ltd.

Preference Articulation by Means of the R2 Indicator - Wagner, Tobias; Trautmann, Heike; Brockhoff, Dimo (Evolutionary Multi-Criterion Optimization)
In multi-objective optimization, set-based performance indicators have become the state of the art for assessing the quality of Pareto front approximations. As a consequence, they are also more and more used within the design of multi-objective optimization algorithms. The R2 and the Hypervolume (HV) indicator represent two popular examples. In order to understand the behavior and the approximations preferred by these indicators and algorithms, a comprehensive knowledge of the indicator’s properties is required. Whereas this knowledge is available for the HV, we presented a first approach in this direction for the R2 indicator just recently. In this paper, we build upon this knowledge and enhance the considerations with respect to the integration of preferences into the R2 indicator. More specifically, we analyze the effect of the reference point, the domain of the weights, and the distribution of weight vectors on the optimization of $μ$ solutions with respect to the R2 indicator. By means of theoretical findings and empirical evidence, we show the potentials of these three possibilities using the optimal distribution of $μ$ solutions for exemplary setups.

R2-EMOA: Focused Multiobjective Search Using R2-Indicator-Based Selection - Trautmann, Heike; Wagner, Tobias; Brockhoff, Dimo (Learning and Intelligent Optimization)
An indicator-based evolutionary multiobjective optimization algorithm (EMOA) is introduced which incorporates the contribution to the unary R2-indicator as the secondary selection criterion. First experiments indicate that the R2-EMOA accurately approximates the Pareto front of the considered continuous multiobjective optimization problems. Furthermore, decision makers’ preferences can be included by adjusting the weight vector distributions of the indicator which results in a focused search behavior.

A Novel Feature-Based Approach to Characterize Algorithm Performance for the Traveling Salesman Problem - Mersmann, O; Bischl, B; Trautmann, Heike; Wagner, M; Bossek, J; Neumann, F (Annals of Mathematics and Artificial Intelligence)
Meta-heuristics are frequently used to tackle NP-hard combinatorial optimization problems. With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesperson problem (TSP). Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.

Server based indoor navigation using RSSI and inertial sensor information - Hoang, Manh Kha; Schmitz, Sarah; Drueke, Christian; Vu, Dang Hai Tran; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Positioning Navigation and Communication (WPNC), 2013 10th Workshop on)
In this paper we present a system for indoor navigation based on received signal strength index information of Wireless-LAN access points and relative position estimates. The relative position information is gathered from inertial smartphone sensors using a step detection and an orientation estimate. Our map data is hosted on a server employing a map renderer and a SQL database. The database includes a complete multilevel office building, within which the user can navigate. During navigation, the client retrieves the position estimate from the server, together with the corresponding map tiles to visualize the user's position on the smartphone display.
Keywords: SQL; navigation; smart phones; wireless LAN; RSSI; SQL database; complete multilevel office building; inertial sensor information; inertial smartphone sensors; map renderer; received signal strength index information; relative position estimates; server based indoor navigation; step detection; wireless-LAN access points; Smartphone; fingerprint; indoor navigation; map tile

A Hidden Markov Model for Indoor User Tracking Based on WiFi Fingerprinting and Step Detection - Hoang, Manh Kha; Schmalenstroeer, Joerg; Drueke, Christian; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a modified hidden Markov model (HMM) for the fusion of received signal strength index (RSSI) information of WiFi access points and relative position information which is obtained from the inertial sensors of a smartphone for indoor positioning. Since the states of the HMM represent the potential user locations, their number determines the quantization error introduced by discretizing the allowable user positions through the use of the HMM. To reduce this quantization error we introduce â??pseudoâ?? states, whose emission probability, which models the RSSI measurements at this location, is synthesized from those of the neighboring states of which a Gaussian emission probability has been estimated during the training phase. The experimental results demonstrate the effectiveness of this approach. By introducing on average two pseudo states per original HMM state the positioning error could be significantly reduced without increasing the training effort.

On the ecological validity of a password study - Fahl, Sascha; Harbach, Marian; Acar, Yasemin; Smith, Matthew (Proceedings of the Ninth Symposium on Usable Privacy and Security)

A Novel Feature-Based Approach to Characterize Algorithm Performance for the Traveling Salesperson Problem - Mersmann, Olaf; Bischl, Bernd; Trautmann, Heike; Wagner, Markus; Bossek, Jakob; Neumann, Frank (Annals of Mathematics and Artificial Intelligence)
Meta-heuristics are frequently used to tackle NP-hard combinatorial optimization problems. With this paper we contribute to the understanding of the success of 2-opt based local search algorithms for solving the traveling salesperson problem (TSP). Although 2-opt is widely used in practice, it is hard to understand its success from a theoretical perspective. We take a statistical approach and examine the features of TSP instances that make the problem either hard or easy to solve. As a measure of problem difficulty for 2-opt we use the approximation ratio that it achieves on a given instance. Our investigations point out important features that make TSP instances hard or easy to be approximated by 2-opt.
Keywords: 2-opt; 90B06; Classification; Feature selection; MARS; TSP

Harmonic analysis on Heisenberg-Clifford Lie supergroups - Hilgert, Joachim; Laubinger, M.; Alldridge, A. (J. London Math. Soc.)

Arbeitsbuch Mathematik für das erste Studienjahr

Lesebuch Mathematik für das erste Studienjahr

The Radon transform and its dual for limits of symmetric spaces - Hilgert, Joachim; Ólafsson, G.

Singular superspaces - Hilgert, Joachim; Alldridge, A.; Wurzbacher, T.

Fostering German-language learners’ constructions of meanings for fractions—design and effects of a language- and mathematics-integrated intervention - Prediger, Susanne; Wessel, Lena (Mathematics Education Research Journal)
Keywords: Education; General Mathematics

Diagnose und Förderung schulpraktisch erproben-am Beispiel Mathematiklernen bei Deutsch als Zweitsprache - Prediger, Susanne; Wessel, Lena; Tschierschky, K; Seipp, B; Özdil, E (Diagnose und individuelle Förderung in der MINT-Lehrerbildung. Das Projekt dortMINT)

Wieso 3/4 von 12, und wo ist der Kreis? Brüche für Teile von Mengen handlungs- und strukturorientiert erarbeiten. - Prediger, Susanne; Krägeloh, N.; Wessel, Lena (Praxis der Mathematik in der Schule)

Sprache und Vorstellungen parallel entwickeln – Wirkungen einer fach- und sprachintegrierten Förderung für sprachlich schwache Lernende - Wessel, Lena (Beiträge zum Mathematikunterricht 2013)

Simulating Cooperative Diversity Protocols for Multi-hop Wireless and Sensor Networks - Khan, Rana Azeem M.; Karl, Holger

Report on Locality in DNS Requests – Evaluation and Impact on Future Internet Architectures - Dannewitz, Christian; Karl, Holger; Yadav, Aditya

Impact of Neuron Models and Network Structure on Evolving Modular Robot Neural Network Controllers - Hamann, Heiko; Stradner, Jürgen; Bredeche, Nicolas; Cazenille, Leo (14th Annual Genetic and Evolutionary Computation Conference, GECCO 2012)
This paper investigates the properties required to evolve Artificial Neural Networks for distributed control in modular robotics, which typically involves non-linear dynamics and complex interactions in the sensori-motor space. We investigate the relation between macro-scale properties (such as modularity and regularity) and micro-scale properties in Neural Network controllers. We show how neurons capable of multiplicative-like arithmetic operations may increase the performance of controllers in several ways whenever challenging control problems with non-linear dynamics are involved. This paper provides evidence that performance and robustness of evolved controllers can be improved by a combination of carefully chosen micro- and macro-scale neural network properties.

Towards Morphological Flexibility: Modular Robotics and Bio-inspired Control - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen (Austrian Robotics Workshop (Operational Programme Slovenia-Austria))
As a contribution to the efforts towards robotic systems of higher flexibility we present our concept of morphologically dynamic robots. Within the projects SYMBRION and REPLICATOR, that focus on modular robotics, we have developed bio-inspired control techniques to achieve new concepts of dynamic, autonomous morphological structures. We propose three modes of coupling between robot modules: swarm, team, and organism mode. We demonstrate our concepts along with simple robot experiments.

On-line, On-board Evolution of Reaction-Diffusion Control for Self-Adaptation - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Zahadat, Payam; Adami, Christoph; Bryson, David M.; Ofria, Charles; Pennock, Robert T. (Alife XIII)

Self-organized pattern formation in a swarm system as a transient phenomenon of non-linear dynamics - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Mathematical and Computer Modelling of Dynamical Systems)

A Hormone-Based Controller for Evaluation-Minimal Evolution in Decentrally Controlled Systems - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Artificial Life)
One of the main challenges in automatic controller synthesis is to develop methods that can successfully be applied for complex tasks. The difficulty is increased even more in the case of settings with multiple interacting agents. We apply the artificial homeostatic hormone system (AHHS) approach, which is inspired by the signaling network of unicellular organisms, to control a system of several independently acting agents decentrally. The approach is designed for evaluation-minimal, artificial evolution in order to be applicable to complex modular robotics scenarios. The performance of AHHS controllers is compared with neuroevolution of augmenting topologies (NEAT) in the coupled inverted pendulums benchmark. AHHS controllers are found to be better for multimodular settings. We analyze the evolved controllers with regard to the usage of sensory inputs and the emerging oscillations, and we give a nonlinear dynamics interpretation. The generalization of evolved controllers to initial conditions far from the original conditions is investigated and found to be good. Similarly, the performance of controllers scales well even with module numbers different from the original domain the controller was evolved for. Two reference implementations of a similar controller approach are reported and shown to have shortcomings. We discuss the related work and conclude by summarizing the main contributions of our work.

Analysis of emergent symmetry breaking in collective decision making - Hamann, Heiko; Schmickl, Thomas; Wörn, Heinz; Crailsheim, Karl (Neural Computing and Applications)

Towards Swarm Calculus: Universal Properties of Swarm Performance and Collective Decisions - Hamann, Heiko; Engelbrecht, Andreas; Birattari, Mauro; Dorigo, Marco; Blum, Christian; Stuetzle, Thomas; Christensen, Anders Lyhne; Gross, Roderich (Swarm Intelligence: 8th International Conference, ANTS 2012)